Can We Measure the Level of Socio-Emotional Competencies of Adolescents? - Iago Portela-Pino; Jose Domínguez-Alonso; Myriam Alvariñas-Villaverde (MDPI AG, 2024)
The present study aimed to evaluate the evidence of validity and reliability of the Social Emotional Competence Questionnaire (SECQ) in Spanish students and to verify if gender is a determining factor in their development. An intentional sampling was carried out on 429 students between 12 and 16 years old. Three factorial structures were tested: the original model, the original re-specified model, and the six-factor model that was achieved. The results maintain that the original re-specified model presented values with the best absolute fit, a slightly more favorable comparative fit, and a parsimonious fit with lower values than the other models. The reliability analysis showed considerable internal consistency. Boys were shown to have better self-management, and girls showed greater management in their social relationships. It is concluded that the questionnaire has adequate psychometric properties and is expressly useful in the population of interest with a relevant weight in the evaluation of socio-emotional competence.